Should I Touch the Customer? Rethinking Interpersonal Touch Effects from the Perspective of the Touch Initiator - Luangrath, Andrea Webb; Peck, Joann; Gustafsson, Anders (Journal of Consumer Research, 2020)
AbstractPrevious research has highlighted the effects of receiving interpersonal touch on persuasion. In contrast, we examine initiating touch. Individuals instructed to touch engage in egocentric projection in which they project their own affective reaction onto their expectations for how the recipient will feel (i.e., empathic forecast), how they appear to the recipient (i.e., metaperception), and the evaluation of the interaction itself (i.e., interaction awkwardness). Touch initiators expect that recipients will feel worse with touch, express concern for how they, themselves, will be perceived, and think that interactions are more awkward. Interestingly, touch recipients do not evaluate these interactions more negatively and leave higher tips after having been touched; touch initiators do not expect this to be the case. As a result, instructed touch initiators (vs. volitional touch initiators) are less (more) likely to engage in subsequent interactions with customers, potentially undermining future service provided to customers. Across five studies, four of which involve actual dyadic interactions, we test the consequences of initiating touch with an inquiry into the effects of interpersonal touch on the initiator. We discuss theoretical and managerial implications.